Hydrophobic ammonium based ionic liquids for efficient extraction of textile dyes from aqueous media: Extraction study and antibacterial evaluation. (April 2023) - Ullah, Saadat; Ali, Zarshad; Khan, Amir Sada; Nasrullah, Asma; Javed, Fatima; Adalat, Bushra; Sher, Naila; Ahmed, Mushtaq; Alshgari, Razan A.; Saleh Mushab, Mohammed Sheikh; Majeed, Saadat
Abstract: Alizarin red S (ARS) extraction from aqueous medium was carried out using hydrophobic ionic liquids (ILs) containing trioctylammonium cation paired with 4- tert -butylbenzoate ([TOA][Butbenz] (IL1), 4-phenylbutanoate ([TOA][PheBut] (IL2), 3-4-dimethylbenzoate ([TOA][DMbenz] (IL3), naphthoate, ([TOA][Naph]) (IL4), salicylate ([TOA][Sali]) (IL5) and nonanedioate ([TOA]2 [Nona]) (IL6). The findings demonstrated that all of the tested ILs were efficient for extracting ARS, however, [TOA]2 [Nona] was more effective than others. For the extraction of ARS from the aqueous phase, the effects of various parameters including the initial pH of the dye solution, contact time, ILs to dye volume ratio (VIL :VW ), dye concentration, temperature, and salt effect were investigated. The spontaneity of the liquid-liquid extraction of ARS from the aqueous phase to the IL phase was confirmed by thermodynamic parameters. More than 90% of the ARS was extracted from the aqueous phase to the IL phase throughout all experiments. Interaction of selected IL with dyes were confirmed using FTIR analysis. The standard bacterial strains of Escherichia coli ( E. coli ) ATCC BAA-2471 (gram negative) and Methicillin-resistant Staphylococcus (MRSA) ATCC 43300 (gram positive) were used for evaluating antibacterial activity. The lower dose (250 ppm), the ILs1, 2, 3, 4, 5, and 6 inhibited 0.40, 1.50, 6.50, 1.50, 2.50, and 0.50 mm growth of E. coli, and 4.0, 2.0, 16.50, 0.40, 5.0, and 3.50 mm growth of MRSA, respectively. The experimental findings confirmed that the present ILs can be utilized as an effective solvent for ARS and other dyes extraction from aqueous media. Graphical abstract: Image 1 Highlights: Hydrophobic ammonium ionic liquids were used for extraction of alizarin red S (ARS) and other dyes. ARS extraction from aqueous to IL phase were more than 90% for all experiments. Thermodynamic study confirmed that the extraction of ARS from aqueous to IL phase is spontaneous. The tested ILs show antimicrobial activities against various types of bacteria.